The Haitian Revolution / . Jean-Bertrand Aristide presents Toussaint L'Ouverture the Haitian Revolution (Verso, 2008)
Cover title: Jean-Bertrand Aristide presents Toussaint L'Ouverture the Haitian Revolution.